MicroRNA-1291 Is Associated With Locoregional Metastases in Patients With Early-Stage Breast Cancer - Escuin, Daniel; López-Vilaró, Laura; Bell, Olga; Mora, Josefina; Moral, Antonio; Pérez, José Ignacio; Arqueros, Cristina; Ramón y Cajal, Teresa; Lerma, Enrique; Barnadas, Agustí (Frontiers in Genetics, 2020)
Evidence that microRNAs (miRNAs) regulate the various steps of metastasis is increasing. Several studies have looked at the miRNA expression profile in primary breast tumors but few have compared primary tumor and sentinel lymph node (SLN) metastasis. We correlated the expression of miRNAs with the SLN status and the outcome of axillary lymph node dissection (ALND) in 60 patients with early breast cancer. We profiled the expression of miRNAs in paired breast tumor samples and SLNs using the NextSeq500 Illumina platform and key findings were validated by qPCR. MultiMiR Bioconductor and Reactome pathways analysis were performed to identify target genes and signaling pathways affected by altered expressed miRNAs. Our results show that nine miRNAs were differentially expressed in tumor tissues (q ≤ 0.05). In tumor samples, a 13.5-fold up-regulation of miR-7641-2 (q < 0.001) and a 2.9-fold down-regulation of miR-1291 (q < 0.001) were associated with tumors with positive SLNs. However, only down-regulation of miR-1291 (q = 0.048) remained significant in paired SLNs samples. Interestingly, a 10.5 up-regulation of miR-1291 in SLNs samples was associated with additional axillary lymph node involvement (q < 0.001). The enrichment analyses showed that canonical and non-canonical WNT pathways and negative regulation of various receptor tyrosine kinases signaling pathways were targets of miR-1291 and supports the role of miR-1291 as a tumor suppressor gene (TSG). Further studies are warranted to investigate the use of miR-1291 as a surrogate biomarker of SLN node metastasis in patients with early-stage breast cancer.